Studies on monitoring the composition of the copolymer by cyclic voltammetry and in situ spectroelectrochemical analysis - Santhosh, P.; Gopalan, A.; Vasudevan, T.; Wen, T.-C. (European polymer journal, 2005)
Electrochemical copolymerization of diphenylamine (DPA) with ortho-toluidine (OT) was carried out in 4 M sulphuric acid medium by cyclic voltammetry. Cyclic voltammograms (CVs) of the copolymer films were recorded to deduce the electrochemical characteristics. In situ UV–visible spectroelectrochemical studies on copolymerization were carried out using indium tin oxide (ITO) coated glass plate as working electrode for different feed ratios of DPA and OT. UV-visible spectral characteristics show clear dependencies on the molar feed composition of DPA or OT used in electropolymerization. Derivative cyclic voltabsorptogram (DCVA) was deduced at the wavelength corresponding to the absorption by the intermediate species and used to identify the intermediates generated during the electropolymerization. The molar composition of DPA and OT units in the copolymer for the copolymers synthesized with different molar feed ratios of DPA and OT was determined by UV–visible spectroscopy. Reactivity ratios of DPA and OT were deduced by using Fineman–Ross and Kelen–Tudos methods and the observed differences in the composition of DPA/OT in the copolymers were correlated with CV characteristics and results obtained from in situ spectroelectrochemical studies.